2018
DOI: 10.1007/s10552-018-1046-8
|View full text |Cite
|
Sign up to set email alerts
|

The association between smoking cessation before and after diagnosis and non-muscle-invasive bladder cancer recurrence: a prospective cohort study

Abstract: BackgroundSmoking is a major risk factor for bladder cancer, but the relationship between smoking cessation after initial treatment and bladder cancer recurrence has been investigated less frequently and not prospectively yet.Methods722 non-muscle-invasive bladder cancer (NMIBC) patients (pTa, pT1, and CIS) from the prospective Bladder Cancer Prognosis Programme (BCPP) cohort, selected in the UK between 2005 and 2011, provided complete data on smoking behavior before and up to 5 years after diagnosis. The impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 44 publications
(53 reference statements)
3
24
0
Order By: Relevance
“…In a prospective cohort study on 722 NMIBC patients, at a median follow-up of 4 years, only 25 patients (14%) of the 174 current smokers at diagnosis quit smoking at any point during follow-up. The authors concluded that smoking cessation after diagnosis did not decrease the risk of recurrence compared to continuing smokers, but the power of the statistical analysis is limited by the small number of ex-smokers [16]. Almost 50% of our patients with primary NMIBC were current smokers and 35% of them definitively stopped, with a smoking cessation rate higher than that reported by other authors [17,18].In a retrospective cohort study, Koshiaris et al [17] found a 21% smoking cessation rate among bladder cancer patients, which is lower than the 27 and 29% detected among upper aerodigestive tract cancer and lung cancer patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective cohort study on 722 NMIBC patients, at a median follow-up of 4 years, only 25 patients (14%) of the 174 current smokers at diagnosis quit smoking at any point during follow-up. The authors concluded that smoking cessation after diagnosis did not decrease the risk of recurrence compared to continuing smokers, but the power of the statistical analysis is limited by the small number of ex-smokers [16]. Almost 50% of our patients with primary NMIBC were current smokers and 35% of them definitively stopped, with a smoking cessation rate higher than that reported by other authors [17,18].In a retrospective cohort study, Koshiaris et al [17] found a 21% smoking cessation rate among bladder cancer patients, which is lower than the 27 and 29% detected among upper aerodigestive tract cancer and lung cancer patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…19,21,25 Clinical studies have found that compared with non-smokers, smokers with bladder cancer have significantly increased cancer recurrence rates and a reduced non-tumor survival period, which may be related to cigarette-induced EMT in bladder cancer cells and promoted cancer stem cells. [26][27][28] Therefore, we have to further understand the molecular mechanism of tobacco in bladder cancer and explore effective preventive drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The sum of existing evidence suggests that smoking may be moderately associated with recurrence [ 6 , 9 12 , 14 , 16 35 , 37 , 39 53 , 60 62 , 64 ]. One meta-analysis of 11 studies of 6,908 NMIBC patients reported an increased risk of recurrence among current smokers (at the time of questionnaire completion, interview, or from patient record review) compared to nonsmokers (hazard ratio [HR] 1.27, 95% confidence interval [CI] 1.09–1.46).…”
Section: Resultsmentioning
confidence: 99%
“…Fifty-seven studies have assessed associations between smoking-related exposures and NMIBC outcomes [6,. Multiple exposure types have been studied, including current versus never, [6, former versus never, [6,60] current versus former, [9][10][11][12][13][14][15][60][61][62][63] and cumulative exposure (e.g., packyears, quantity/day, cigarette index) [9-13, 16-19, 37, 38, 60, 64].…”
Section: Smokingmentioning
confidence: 99%